Development and implementation of a website assessment tool to evaluate policies and resources for sexual assault and alcohol use on US college campuses - Elizabeth A. Walker; Regina Futcher; Naomi Segel; Nandana Menon; Julia Vroman; Alyssa E. Gribov; Kayla Ortiz; Robert W. S. Coulter; Christina F. Mair; Elizabeth Miller; Rachel E. Gartner (BMC Global and Public Health)
Abstract Background Sexual assault on college campuses is a major public health concern. Over half of incidents of sexual violence on college campuses occur in the context of victim or perpetrator alcohol use. Students who have experienced sexual violence, including in the context of alcohol use, are likely to seek information about sexual violence resources and services online. Methods We developed a Website Assessment Tool to capture a student’s perspective when navigating campus sexual violence and alcohol websites to find resources and services. The tool evaluates (1) accessibility, (2) comprehensibility, and (3) inclusivity of sexual violence and alcohol prevention information and resources. Alcohol policies and alcohol-related campus resources are also evaluated for linkage to sexual violence information. We assessed websites from 36 college campuses across the USA participating in a sexual violence prevention study. Results The accessibility, comprehensibility, and inclusivity of educational content, services, and supports related to sexual violence and alcohol use varied widely. Websites with Title IX regulations, outlining protections against sex-based discrimination, were easily accessible for each school. Identifying whether services were confidential was inconsistent. Sexual violence resources were difficult to locate or embedded in lengthy text and difficult to comprehend, terms were not always defined, and descriptions of services were not explicitly inclusive of diverse populations. The alcohol policies for each school were accessible. Most campuses’ (97%) alcohol policies and resources did not include sexual violence-related information or link alcohol-related information to their student counseling or health center website. Conclusions This Website Assessment Tool may be useful for college campuses seeking to optimize their students’ receipt of information related to sexual violence and alcohol to increase awareness of sexual violence support services and to connect survivors with resources. Both sexual violence and alcohol use prevention and intervention strategies should include the prevalence and increased risk of alcohol-involved sexual violence on college campuses to help reduce alcohol-involved sexual violence and ensure survivors are connected to supports and services with few to no barriers.